PENGARUH PENGADOPSIAN INTERNATIONAL FINANCIAL REPORTING STANDARD (IFRS) TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2011 - 2012) - Abhiyoga Narendra; Haryanto Haryanto (Diponegoro Journal of Accounting, 2013)
The research aimed to give empirical evidence concerning the effect of the IFRS adoption on earnings management and the test of the difference of earnings management level between before and after the adoption. The research objects were the manufacturing companies listed in Indonesia Stock Exchange for 2 years (2011-2012). The main variables in this research are IFRS and earnings management. The research also includes several control variables i.e. size, financial leverage, market to book value and institutional investors. The data were analyzed by using multiple regression analysis and different t-test analysis. In this research, the adoption of IFRS indicates the positive effect on earnings management. The result of different test analysis also indicates that there is a statistically significant difference of earnings management level between before and after the adoption of IFRS. The other result indicates that among the four control variables, financial leverage indicate the positive effect on earnings management. Market to book value indicates a negative effect, whereas institutional investor is found not to have significant effect. Based on this research concluded that the adoption of IFRS has not fully guaranteed a decrease in earnings management yet.